Syariah principles in Islamic banking: with special reference to BIMB / Wan Asma’a Wan Abu Bakar - Wan Abu Bakar, Wan Asma’a (Research Management Institude, 1993)
BIMB, the only bank in Malaysia that can call itself an Islamic bank, practise its activities and trade according to the Islamic law. The Bank exists andcoperates in a secular environment. It faces lots of obstacles and has to compete with many non-Islamic banks which already have a strong foothold in the local banking sector. From the Bank's brochures and pamphlets, it is clear that BIMB is to provide facilities and services to the public, the Muslims especially, according to the principles of Shariah. The National Steering Committee Report, a report from a group that was given a task to spearhead the formation of an Islamic bank, in elaborating the concept of an Islamic bank in Malaysia stated that "the banking operation in accordance with islam are conclusive because it will achieve the basic objective, that is, the interest of the Muslim community. Any activity which contradict this objective is considered as misuse of wealth that has been entrusted to us by Allah and this implies a betrayal of His command". The running of BIMB, no doubt, is towards achieving its objectives, but is BIMB really trying to achieve the main objective as stated in the report, or does BIMB is preoccupied with its high rate of profit to impress the public and other commercial banks?